Oral L-cysteine ethyl ester (LCEE) reduces amoebic gill disease (AGD) in Atlantic salmon Salmo salar - Roberts, SD; Powell, MD (2005)
There is a need for the development of alternative therapeutic treatments for amoebic gill disease (AGD) in Atlantic salmon Salmo salar L. to maintain the sustainability of the Tasmanian Atlantic salmon aquaculture industry. This study aimed to assess the effects of the mucolytic drug L-cysteine ethyl ester (LCEE) on marine Atlantic salmon mucus and whether or not it may have a therapeutic advantage for the alleviation of AGD when administered orally. We also aimed to document any physiological consequences of LCEE. Results showed that LCEE significantly decreased the viscosity of marine Atlantic salmon mucus both in vitro, where LCEE concentration showed a negative relationship to mucus viscosity (R2 = 0.95 at 11.5 s-1), and in vivo. Oral administration of LCEE at 52.7 mg LCEE kg-1 fish d-1 over 2 wk significantly delayed the progression of AGD-associated pathology during an aggressive, cohabitation induced, laboratory infection. Medicated fish had approximately 50% less gill filaments affected by AGD than control fed fish at 3 d post-infection when assessed using histology. Palatability of medicated feed was shown to be approximately 65 % of control feed. No osmoregulatory disturbance was seen in medicated fish, although blood and whole body flux data indicated a slight acidosis coinciding with an increased plasma total ammonia concentration. However, both variables were within a tolerable physiological range and returned to control levels 3 d post-cessation of medicated feed. LCEE holds potential as an in-feed additive when administered over 2 wk prior to infection to delay the progression of AGD associated pathology. From the parameters measured, LCEE seems to have minimal physiological consequences after 2 wk of administration. Â© Inter-Research 2005.